2014
DOI: 10.1063/1.4865967
|View full text |Cite
|
Sign up to set email alerts
|

Line interference effects using a refined Robert-Bonamy formalism: The test case of the isotropic Raman spectra of autoperturbed N2

Abstract: A symmetrized version of the recently developed refined Robert-Bonamy formalism [Q. Ma, C. Boulet, and R. H. Tipping, J. Chem. Phys. 139, 034305 (2013)] is proposed. This model takes into account line coupling effects and hence allows the calculation of the off-diagonal elements of the relaxation matrix, without neglecting the rotational structure of the perturbing molecule. The formalism is applied to the isotropic Raman spectra of autoperturbed N2 for which a benchmark quantum relaxation matrix has recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Note that a similar result was obtained from the semi-classical approach of Ref. 24, corroborating the necessity of taking into account the translational-rotational coupling in such cases of high inelasticity.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Note that a similar result was obtained from the semi-classical approach of Ref. 24, corroborating the necessity of taking into account the translational-rotational coupling in such cases of high inelasticity.…”
Section: Resultssupporting
confidence: 84%
“…24 where it was not possible to obtain relaxation matrix elements verifying at the same time detailed balance and the sum rule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a slightly different approach was proposed [227], based on the coordinate representation. It was first applied to isotropic Raman transitions of pure N 2 [227,228] for which a comparison with benchmark quantum results [195,229] was possible. This analysis showed that accounting for the line coupling reduces the line widths by about 15 % with a much better agreement with the quantum results.…”
Section: Refined Semi-classical Robert-bonamy (Rb) Formalismmentioning
confidence: 99%
“…More recently, Ma et al [20] have shown that by considering effects from the line coupling in the standard [12] RB method, one is able to obtain a much better agreement with experimental values at least for self-perturbed nitrogen isotropic Raman lines. The latter study has been completed by a comparison of the full relaxation matrix as obtained with this refined method with quantum dynamical calculations [24,25]. Meanwhile, this refined version of semi-classical RB model has been adapted to the case of IR lines [26].…”
mentioning
confidence: 99%